2005
DOI: 10.1111/j.1553-2712.2005.tb01475.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Judgment of Emergency Physicians in the Management of Patients with Acute Headache

Abstract: Objectives: There is little evidence guiding physicians in the evaluation of acute headache to rule out nontraumatic subarachnoid hemorrhage (SAH). The authors assessed emergency physicians in: 1) their pretest accuracy for predicting SAH, 2) their comfort with not ordering either head computed tomography (CT) or lumbar puncture (LP) in patients with acute headache, and 3) their comfort with not ordering head CT before performing LP in patients with acute headache. Methods: This two-and-a-half-year prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
2
17
1
Order By: Relevance
“…Whereas clinical judgment is likely to play an important role in the accurate diagnosis of SAH in the ED, 26 standardization of the diagnostic approach to potential SAH patients may not fully address the problem. Current efforts to derive a clinical decision rule to rule out SAH in headache patients have been carried out among patients attending teaching hospital sites, 32,33 and the effectiveness of rules could be limited if their implementation or interpretation varies between community and teaching hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas clinical judgment is likely to play an important role in the accurate diagnosis of SAH in the ED, 26 standardization of the diagnostic approach to potential SAH patients may not fully address the problem. Current efforts to derive a clinical decision rule to rule out SAH in headache patients have been carried out among patients attending teaching hospital sites, 32,33 and the effectiveness of rules could be limited if their implementation or interpretation varies between community and teaching hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Overall mortality is 25% in 24 hours and 50% within six months. Of the survivors, 42% are left with neurologic sequelae (Perry et al, 2005).…”
Section: Results:-mentioning
confidence: 99%
“…ASAH has an annual incidence of 1 to 2.5 per 10,000 persons. It occurs in young people, with a median age of 50 years (Perry et al, 2005).…”
Section: Results:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation typically includes imaging studies and a spinal fluid examination (Table 3.7). In an interesting study, ED physicians evaluated 747 headache patients, 77% of whom reported this was their "worst headache" [16]. SAH was eventually diagnosed in 50 of these patients.…”
Section: Pearl For the Practitionermentioning
confidence: 99%